2014
DOI: 10.1103/physreve.89.061301
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic integrators for spin systems

Abstract: We present a symplectic integrator, based on the implicit midpoint method, for classical spin systems where each spin is a unit vector in R 3 . Unlike splitting methods, it is defined for all Hamiltonians and is O(3)-equivariant, i.e., coordinate-independent. It is a rare example of a generating function for symplectic maps of a noncanonical phase space. It yields a new integrable discretization of the spinning top.Symplectic integrators for the computer simulation of Hamiltonian dynamics are widely used in co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Most symplectic integrators require that the equations are formulated in terms of pairs of canonical coordinates, i.e. a colection of phase-space coordinates χ i , π i , with i some labelling index, such that {χ i , π j } = δ i j (however, there do exist symplectic integrators for special classes of systems that require no such coordinates [53,52]).…”
Section: Importance Of Canonical Coordinates and Dirac Bracketsmentioning
confidence: 99%
“…Most symplectic integrators require that the equations are formulated in terms of pairs of canonical coordinates, i.e. a colection of phase-space coordinates χ i , π i , with i some labelling index, such that {χ i , π j } = δ i j (however, there do exist symplectic integrators for special classes of systems that require no such coordinates [53,52]).…”
Section: Importance Of Canonical Coordinates and Dirac Bracketsmentioning
confidence: 99%
“…In [17] it is shown that also (15) coincides with (16) when B(·) = ∇H(·), for some Hamiltonian function H : R 3 → R constant on the rays (which implies B(·) to be orthogonal to the rays). In this case, (16) is known to be symplectic, whereas this fails for general Hamiltonian H. Therefore, (14) can be seen as the second order correction of (16) to be symplectic for any Hamiltonian H.…”
Section: 3mentioning
confidence: 99%
“…While it is very difficult or impossible to find an effective symplectic time-reversible integrator for the semiclassical spin dynamics 48,49 , this is not a problem for the auxiliary spin-dynamics. We combine the velocity Verlet method 50 and a spin rotation scheme to obtain an efficient numerical integration algorithm that is timereversible, area-preserving and preserves spin length.…”
Section: Methodsmentioning
confidence: 99%